GAMBARAN RESIKO TINGGI KEHAMILAN - Asmidar " Wati; Sri " Utami; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract High risk pregnancy is a pregnancy risk or a greater danger at the time of pregnancy and childbirth. An estimated  women die from complications of pregnancy around the world every day. High risk in pregnancy are influenced by various factors such as the medical and non-medical. The division-risk pregnancy included maternal age, history of pregnancy, labor history and history of maternal illness. The purpose of this research was to describe high risk pregnancy at Kelurahan Bagan Besar. The methods used in this research was descriptive, with accidental sampling technique. Sample of this study was 81 respondents and taken corresponding with inclusion criteria. The univariate analysis was conducted to know the result showed most of respondents The analysis used univariate to determine the frequency distribution. The result showed expecting her first child <20 years and> 35 years 7 respondents (25%) and low risk pregnancy 53 respondents (65,4%). The results of this study recommend that the describe gets a high risk pregnancy as the first step to more beware and alert in the childbirth of secure.